Preserving Environmental Sustainability in Pisitan Village, Cianjur Regency - Munawar, Aini Nurazijah; Niscahyo, Dwi Ratno; Nuraeni, Fitria; Oktaviano, Giovani; Jannah, Hadiqotul; Diantha, Kineisha Malika Priya; Rohman, Muhammad Habibur; Fuadi, Muhammad Hafiz Rasinul; Syuhada, Muhammad Nabil; Pratusha, Puspa Dewi; T, Tamami; S, Suhendar; Herdiana, Dian (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Pancasila as the basis of the Indonesian state is not only the basis for national unity, but also as a moral guide in preserving nature.The first principle, Belief in One Almighty God, teaches respect for God's creation which is manifested in environmental conservation.Second, Just and Civilized Humanity, demands awareness to protect nature so that it remains habitable for present and future generations.The third principle, Indonesian Unity, is key because nature conservation knows no territorial boundaries, requiring the cooperation of all citizens regardless of ethnicity, religion or origin.Fourth, democracy led by wisdom in deliberation and representation, encouraging community participation in decision making related to the environment.Fifth, Social Justice for All Indonesian People, ensuring that the benefits of nature conservation are felt equally.Through consistent application of Pancasila values, the Indonesian nation can strengthen unity while protecting biodiversity and ecosystems which are the nation's treasures.